Chapter The Use of Unmanned Aerial Vehicles by Urban Search and Rescue Groups - Półka, Marzena (InTechOpen, 2018)
In the case of natural or man-made disaster, the top priority of urban search and rescue (USAR) groups is to localise the victim as quickly as possible. Even minutes might play a crucial role in the victim's survival. A number of standard operating procedures may be applied to achieve best performance. Rescue dogs are trained to search for alive victims; special inspection cameras are used, before heavy equipment is being implemented. To improve the effectiveness of USAR group operations, innovative technologies might be implemented. The most recent solution is currently designed in MOBNET project, founded by EU under the Horizon 2020 programme. The scope of the project is to combine both cellular technology and early Galileo services to localise the smartphones of potential victims. Integration tests give some promising outcomes. The following chapter looks at typical applications, real needs of public services as well as the performance of the novel system.